Respuesta :

Answer:

B. Taking square root of both sides

Step-by-step explanation:

The first step given to us is

[tex](x+\frac{b}{2a} )^2=\frac{b^2-4ac}{4a^2}[/tex]

When we take square root of both sides we obtain;

[tex]x+\frac{b}{2a}=\pm \sqrt{\frac{b^2-4ac}{4a^2} }[/tex]

Therefore the corect answer is B

Answer:

Choice B is the answer.

Step-by-step explanation:

We have given two step.

(x+b/2a)² = b²-4ac / 4a²      Step I

a+b/2a  = ±√b²-4ac / 4a²      Step II

We have to choose the method to move step I to step II.

Taking square root to both sides of step I, we have

√(x+b/2a)² = √b²-4ac/4a²

As we know that

√x² = ±x

(x+b/2a) = ±√b²-4ac / 4a² and we get the step II.

Hence, the answer is choice B.

ACCESS MORE